Genetic diversity in table grapes based on RAPD and microsatellite markers - Leão, Patrícia Coelho de Souza; Motoike, Sérgio Yoshimitsu (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to analyze the genetic diversity of 47 table grape accessions, from the grapevine germplasm bank of Embrapa Semiárido, using 20 RAPD and seven microsatellite markers. Genetic distances between pairs of accessions were obtained based on Jaccard's similarity index for RAPD data and on the arithmetic complement of the weighted index for microsatellite data. The groups were formed according to the Tocher's cluster analysis and to the unweighted pair-group method with arithmetic mean (UPGMA). The microsatellite markers were more efficient than the RAPD ones in the identification of genetic relationships. Information on the genetic distance, based on molecular characteristics and coupled with the cultivar agronomic performance, allowed for the recommendation of parents for crossings, in order to obtain superior hybrids in segregating populations for the table grape breeding program of Embrapa Semiárido.